Twenty-Four-Hour Heart Rate Is a Trait but Not State Marker for Depression in a Pilot Randomized Controlled Trial With a Single Infusion of Ketamine - Schiweck, Carmen; Lutin, Erika; De Raedt, Walter; Cools, Olivia; Coppens, Violette; Morrens, Manuel; Van Hoof, Chris; Vrieze, Elske; Claes, Stephan (Frontiers in Psychiatry, 2021)
Background: Abnormalities of heart rate (HR) and its variability are characteristic of Major Depressive Disorder (MDD). However, circadian rhythm is rarely taken into account when statistically exploring state- or trait-markers for depression. Methods: Sixteen treatment resistant patients with MDD and 16 age and sex matched controls completed an in depth multi-day psychophysiological recording before and after a single treatment with the rapid-acting anti-depressant ketamine or placebo (clinical trial registration available on https://www.clinicaltrialsregister.eu/ with EUDRACT number 2016-001715-21). Circadian rhythm differences of HR and the root mean square of successive differences (RMSSD) were compared between groups and were explored for classification purposes. Baseline HR/RMSSD were tested as predictors for treatment response and physiological measures were assessed as state marker. Results: Patients showed higher HR and lower RMSSD alongside marked reductions in HR amplitude and RMSSD variation throughout the day. Excellent classification accuracy was achieved using HR during night (90.6%). A positive association between baseline HR and treatment response (r= 0.55, p=0.046) pointed towards better treatment outcome in patients with higher HR. HR also decreased significantly following treatment but was not associated with improved mood after ketamine treatment. Limitations: Our study had a limited sample size and patients were treated with concomitant antidepressant medication. Conclusion: Patients with depression show a markedly reduced amplitude for HR and dysregulated RMSSD fluctuation. Higher HR and lower RMSSD in depression remain intact throughout a 24-hour day, with highest classification accuracy during the night. Baseline HR levels show potential for treatment response prediction, but in this study, did not show potential as state marker.